JUCO (Jump Counting) learning strategies resolve student learning in integer materials - Isti Winarni; Lakna Tulas'un (LINEAR: Journal of Mathematics Education, 2025)
The impact of curriculum changes requires teachers to think creatively and innovatively in delivering learning materials. The new curriculum, The Independent Curriculum, encourages the packaging of learning by paying attention to student learning styles, aiming that all learners are facilitated in their learning. Students in the sixth grade of PTQ Annida Salatiga Elementary School still have difficulties understanding the concept of integer operations, impacting learning outcomes that are still much below the standard value or KKM that has been determined. For this reason, teachers innovate learning using JUCO (Jump Counting). The purpose of using this media is to facilitate and improve students' learning outcomes with more fun and meaningful learning. The method used in this study is descriptive quantitative, with research instruments used as pre-test and post-test, where the results will be analyzed. The study was conducted on 21 Elementary School students in Grade IV. The result of using JUCO (Jump Counting) is an increase in learning outcomes by 18.98%. JUCO makes it easier for teachers to convey material and learners in learning, making it easier to accept the concept of the material presented. The impact of the use of JUCO (Jump Counting) from affective and psychomotor aspects, including collaborative.